Making Farmland Work for Economic Development in Uzbekistan - Zorya, Sergiy; Ilina, Darya (World Bank, Washington, DC, 2019)
What is produced on farmland is critical to the agriculture sector outcomes. If other objectives, such as farm incomes, jobs, water security, were considered as important as producing more of wheat and cotton in Uzbekistan, the farmland use structure will have looked differently. This report offers an example of more balanced allocation of farmland, which can increase agricultural production by 51 percent, employ 16 percent more people in primary agriculture, and save 11 percent water by 2030. All this can be achieved without undermining food security (for example, wheat supply) and development of textile industry. Outlooks are subject to uncertainty and the identified gains may not be necessarily realized. Yet, the benefits of more balanced farmland use are too large to be ignored for the future of agriculture development in Uzbekistan.